2004
DOI: 10.1677/erc.1.00764
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase as a new target for the treatment of hormone-refractory prostate cancer

Abstract: Prostate cancer is the leading cause of cancer-related deaths in men. Androgen ablation is the mainstay of treatment for advanced prostate cancer. This therapy is very effective in androgen-dependent cancer; however, these cancers eventually become androgen independent, rendering anti-androgen therapy ineffective. The exploration of novel modalities of treatment is therefore essential to improve the prognosis of this neoplasia.Telomeres are specialized heterochromatin structures that act as protective caps at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 113 publications
(47 reference statements)
1
17
1
Order By: Relevance
“…Our results in MCF-7 cells were not consistent with several reports which showed that quercetin, H-89 or herbimycin A did not significantly inhibit telomerase enzyme activity (30). Kudo et al showed that, although 100 µM quercetin could not influence the HSP90 expression, which is essential for telomerase enzyme acitivity, quercetin might affect the interaction between HSP90 and actin filaments without influencing HSP90 expression itself.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results in MCF-7 cells were not consistent with several reports which showed that quercetin, H-89 or herbimycin A did not significantly inhibit telomerase enzyme activity (30). Kudo et al showed that, although 100 µM quercetin could not influence the HSP90 expression, which is essential for telomerase enzyme acitivity, quercetin might affect the interaction between HSP90 and actin filaments without influencing HSP90 expression itself.…”
Section: Discussioncontrasting
confidence: 99%
“…17 A previous study showed that OBP-401 in combination with docetaxel efficiently enhanced the antitumor efficacy in an in vivo human lung tumor model. 12 Because telomerase activity is reportedly higher in aggressive prostate cancer than in non-aggressive forms, 18 we speculate that progressive prostate cancer, such as androgen-independent prostate cancer, preferentially responds to OBP-301 treatment. These findings thus suggest that the concomitant use of docetaxel may therefore augment the effect of OBP-301 against prostate cancer.…”
Section: Discussionmentioning
confidence: 98%
“…In this sense, our results suggest that PZsc may have a stronger ability to promote PCa progression. Several groups have reported that sex hormones can regulate hTERT expression, [54][55][56] but the mechanism is unknown. We also found that E2 increased hTERT mRNA expression.…”
Section: Differential Effects Of Pzsc and Tzsc On Pc3 Cellsmentioning
confidence: 99%